Pengembangan Media Pembelajaran Board Game “Ular Tangga” Pada Materi Trigonometri Kelas X SMA - Martin Alex; Tri Buana Tirta Adi Luhur; Muhammad Rifdan (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Interesting learning media can make the learning atmosphere less boring and can improve learning outcomes. The aim of this research was to develop the learning media Snakes and Ladders, which is one of the most famous types of board games throughout the world, for high school (SMA) students as a learning tool that is expected to be valid, effective and practical to use in the learning process. learning Trigonometry material. This research method uses Research Development (R&D) with the ADDIE model which is built in 5 stages: Analyze, Design, Development, Implementation, Evaluate. The subjects of this research were 40 active class X students at SMAN 93 Jakarta. This snake and ladder was developed based on student learning styles. The "Snakes and Ladders" board game was declared a valid learning medium by material and media experts, with an extraordinary category of 94% and 86%. The research results show that the practicality index obtained is in the very good category (96%) and the significance result of the paired t-test is 0.000 (less than 0.005) supported by the average posttest value being higher than the pretest. Based on this development research, it can be concluded that the "Snake and Ladder" board game media developed is valid, practical and effective for the learning process as a learning tool, especially for high school students on Trigonometry material.